Erratum to: 36th International Symposium on Intensive Care and Emergency Medicine: Brussels, Belgium. 15-18 March 2016 - (:unkn) unknown (My University, 2016)
[This corrects the article DOI: 10.1186/s13054-016-1208-6.].